2015
DOI: 10.1038/srep13809
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric and Solid Lipid Nanoparticles for Sustained Release of Carbendazim and Tebuconazole in Agricultural Applications

Abstract: Carbendazim (MBC) (methyl-2-benzimidazole carbamate) and tebuconazole (TBZ) ((RS)-1-(4-chlorophenyl)-4,4-dimethyl-3-(1H-1,2,4-triazol-1-ylmethyl)pentan-3-ol) are widely used in agriculture for the prevention and control of fungal diseases. Solid lipid nanoparticles and polymeric nanocapsules are carrier systems that offer advantages including changes in the release profiles of bioactive compounds and their transfer to the site of action, reduced losses due to leaching or degradation, and decreased toxicity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(64 citation statements)
references
References 49 publications
2
54
0
1
Order By: Relevance
“…Previous studies have shown similar to our stability results of NPs that the particle size was decreased depending on times. The particle size of PLA nanocapsules was changed from 542 nm to 490 nm after 90 days (Campos et al, 2015). Surface modified PLGA NPs with herceptin decreased the particle size depending on herceptin degradation (Yu et al, 2016).…”
Section: Characterization Of Cs-coated Plga-poloxamer Npsmentioning
confidence: 99%
“…Previous studies have shown similar to our stability results of NPs that the particle size was decreased depending on times. The particle size of PLA nanocapsules was changed from 542 nm to 490 nm after 90 days (Campos et al, 2015). Surface modified PLGA NPs with herceptin decreased the particle size depending on herceptin degradation (Yu et al, 2016).…”
Section: Characterization Of Cs-coated Plga-poloxamer Npsmentioning
confidence: 99%
“…Moreover, the composition of the formulation used in this study, namely tripalmitin as lipid matrix and PVA as emulsifier, has been shown to be suitable as a sustained delivery system of bioactive molecules due to their good physicochemical characteristics such as size, zeta potential, high encapsulation efficiency, etc [20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…In the case of medical applications, a (relatively) high production cost can be accepted, but for agricultural production that is not possible and nanomaterials should be produced in great amounts and for a very low price. Promising works in this direction are those dealing with natural polymers such as chitosan (Grillo et al, 2014;Maruyama et al, 2016) and alginate (Silva et al, 2010), and lipids (Pérez-de-Luque et al, 2012;Campos et al, 2015a;de Oliveira et al, 2015). This kind of polymers are easily synthesized and produced from natural existing compounds like chitin from crustaceans' exoskeleton (for chitosan) and from brown algae (for alginate) (for a review, see Campos et al, 2015b), and they can be obtained in high amounts with a low cost.…”
Section: But the Room Is Too Bigmentioning
confidence: 99%